Risk of urothelial cancer death among people using antihypertensive drugs—a cohort study from Finland. (4th July 2019) - Santala, Eerik E. E.; Kotsar, Andres; Veitonmäki, Thea; Tammela, Teuvo L. J.; Murtola, Teemu J.
Abstract: Background: To analyse the association between antihypertensive (anti-HT) drug use and risk of urothelial cancer (UC) death. UC occurs as bladder cancer (BCa) and upper tract urothelial carcinomas (UTUCs). Hypertension is a suggested risk factor for BCa and may impair disease prognosis. However, it's unclear if use of anti-HT drugs could improve the prognosis of UC. Materials and methods: This study evaluated the association between use of anti-HT drugs and UC survival among 14, 065 participants diagnosed with BCa and 1080 with UTUC during 1995–2012 in Finland. It analyzed data using the multivariable adjusted conditional Cox regression model. Results: Angiotensin-receptor (ATR) blocker use before BCa diagnosis was associated with slightly decreased risk of BCa death (HR = .81, CI = .71–0.93). The association was dose-dependent and it decreased in association with elevated intensity of ATR-blocker use. Post-diagnostic use of ATR-blockers was similarly associated with better survival compared to non-users (HR = .81, CI = .71–0.92. Interestingly, use of calcium-channel blockers also associated with better survival and the risk of BCa death decreased with increasing intensity of use (HR = .67, CI = .52–0.86 for highest intensity). Conclusions: This large population-based cohort suggests decreased risk of BCa death among ATR-blocker and calcium-channel blocker users. The risk association among ATR-blockers and calcium-channel blockers was dose-dependent suggesting a causal explanation. Similar risk associations are not observed for other anti-HT drug users, which may suggest a direct effect of ATR blocker or calcium-channel blocker use. Further studies are needed to elucidate the potential anticancer mechanism.